Transit Access to Subsidized Food Stores in the U.S. Midwest. Issue 1 (2nd January 2023) - DeJohn, Amber D.; Widener, Michael J.; Shannon, Jerry
Abstract : In the United States, low-income individuals and some racial and ethnic minorities have higher rates of transit use and food insecurity. The Supplemental Nutrition Assistance Program (SNAP), which provides low-income households with money for groceries at authorized retailers, creates a unique food procurement environment for participants. In this article, transit networks' effect on access to SNAP retailers is assessed by calculating transit travel times to all transitable SNAP stores of census block groups (CBGs) in thirty-three metropolitan areas in the U.S. Midwest. Low transit access CBGs are identified and compared to U.S. Department of Agriculture (USDA) low-income, low-access (LILA) census tracts. Store type transit access ratios are analyzed to further specify disproportionate access to healthy food retailers. Findings indicate low transit access is experienced in fringe-urban, majority white, car-dependent CBGs. Approximately 24, 380 people receiving public assistance, 145, 636 Black people, 135, 731 non-Black Hispanic people, and 108, 325 low-income people live within these CBGs, however. The USDA's LILA census tracts are more expansive than this study's low-income, low-transit-access (LILTA) tracts. Despite being classified as rural, LILTA-only tracts had sixty-eight households without a vehicle, on average. Future research and policy should engage populations in suburban and exurban regions to accommodate transportation needs of a nonnegligible portion of potentially food-insecure households.